Effect of Monopoly Practice in Relation to Merger - Yolanda Mona Salainti,; Feibe Engeline Pijoh, (Technium Social Sciences Journal, 2023)
This research is included in the category of normative research, namely research conducted using a library research approach, namely by taking material from legal literature, laws and regulations and other written sources. In an effort to grant permits and supervise the implementation of mergers, as well as prohibit the implementation of a merger if it is considered that the merger may result in restrictions on freedom/fair competition and create a monopoly situation. The research objectives to be achieved are (1) to obtain clear data regarding monopoly practices in relation to mergers. (2) To find out and reveal the things that cause monopolistic practices. The type of research that will be used in writing this law is normative juridical research.